Influence of replacement hormonal therapy on neutrophils priming by TNF-α - Stetkiewicz, Tomasz; Połać, Ireneusz; Stachowiak, Grzegorz; Jędrzejczyk, Sławomir; Romanowicz-Makowska, Hanna; Surkont, Grzegorz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2004)
Objective: To compare effects of oral and transdermal HRT in postmenopausal women on priming of neutrophils by TNF-α, measured in peripheral blood using the method of chemiluminescency. Material and methods: Study group consists of postmenopausal women diagnosed and treated in Outpatient Clinic and Clinical Department of Gynaecology and Menopausal Diseases in our institute. 46 women were treated oral HTR and 43 women were on transdermal HRT. Oxydative burst of neutrophils was evaluated in 20 ml peripheral blood sample before, after 3 and 6 months of this therapy. Oxydative burst was observed after neutrophils acivation with stimulators: fMLP, PMA and zymosan with or without previous preactivation with 10 ng. TNF-α. Chemiluminescency associated with oxydation burst was measured with Luminometr 1251, BioOrbit, Turku, Finland in stable temperature during 30 minutes (15 readings). Result sand Conclusions: Decreasing effect of HRT on priming of neutrophils by TNF-a did not depend on which way was HRT administrated.